The application prospects of sacha inchi (Plukenetia volubilis linneo) in rheumatoid arthritis - Wang, Min; Xiang, Yin-Hong; Liu, Mei; Jiang, Shan; Guo, Jia-ying; Jin, Xiao-yan; Sun, Hui-feng; Zhang, Ning; Wang, Zhi-Gang; Liu, Jian-xin (Frontiers in Pharmacology, 2024)
Sacha Inchi (Plukenetia volubilis L) (SI) is a traditional natural medicine from tropical rainforests of Amazon region in South America. As a raw material for edible oil, it has various pharmacological effects such as antioxidant, anti-inflammatory, hypolipidemia, and blood pressure lowering, which have attracted increasing attentions of pharmacists. This has prompted researchers to explore its pharmacological effects for potential applications in certain diseases. Among these, the study of its anti-inflammatory effects has become a particularly interesting topic, especially in rheumatoid arthritis (RA). RA is a systemic autoimmune disease, and often accompanied by chronic inflammatory reactions. Despite significant progress in its treatment, there is still an urgent need to find effective anti-RA drugs in regard to safety. This review summarizes the potential therapeutic effects of SI on RA by modulating gut microbiota, targeting inflammatory cells and pathways, and mimicking biologic antibody drugs, predicting the application prospects of SI in RA, and providing references for research aimed at using SI to treat RA.